Mitochondria-derived reactive oxygen species induce over-differentiation of neural stem/progenitor cells after non-cytotoxic cisplatin exposure - Bustamante-Barrientos, Felipe A.; Lara-Barba, Eliana; Herrera-Luna, Yeimi; García-Guerrero, Cynthia; Silva-Pavez, Eduardo; Morales-Reyes, Jonathan; Araya, María Jesús; Yanten-Fuentes, Liliana; Luque-Campos, Noymar; Altamirano, Claudia; Vega-Letter, Ana María; Luz-Crawford, Patricia (Frontiers in Cell and Developmental Biology, 2025)
BackgroundNeural stem and progenitor cells (NSPCs) are crucial for nervous system development and self-renewal. However, their properties are sensitive to environmental and chemical factors, including chemotherapy agents like cisplatin, an FDA-approved drug used to treat cancer. Cisplatin inhibits DNA replication but can cause side effects such as nephrotoxicity, ototoxicity, and neurotoxicity. While its cytotoxic effects are well understood, the impact of non-cytotoxic cisplatin concentrations on NSPC differentiation remains unclear.MethodsThis study examined how non-cytotoxic cisplatin exposure influences NSPC differentiation and mitochondrial activity, specifically through reactive oxygen species (ROS) generation. Mitochondrial activity was analyzed via tetrazolium salt (MTT) assay, ATP biosynthesis, mitochondrial membrane potential (ΔΨm), biomass, and ROS production. Glycolytic activity was assessed by extracellular acidification and lactate production. Self-renewal capacity and differentiation were measured using flow cytometry and confocal microscopy. Mitochondrial ROS generation was modulated with Mito-TEMPO.ResultsAfter 24 h of non-cytotoxic cisplatin exposure (5 μM), mitochondrial activity increased, as shown by higher MTT conversion, ATP content, ΔΨm, biomass, and ROS levels. Despite a stabilization of mitochondrial activity and ROS production by 72 h, this exposure impaired cell cycle progression, self-renewal, and enhanced differentiation toward neuronal and glial lineages. Inhibition of mitochondrial ROS production reduced neuronal and glial differentiation but did not restore self-renewal or cell cycle progression. A decrease in extracellular acidification and lactate production indicated a shift from glycolysis to mitochondrial respiration.DiscussionEven at subtherapeutic levels, cisplatin disrupts NSPC integrity, driving differentiation through mitochondrial ROS-dependent mechanisms. While inhibiting ROS reduced differentiation, it did not restore NSPC proliferation. These findings highlight the vulnerability of NSPCs to cisplatin, even at doses considered safe. The metabolic shift toward mitochondrial respiration may contribute to this differentiation bias. Future research on co-administration of antioxidant agents during chemotherapy could protect NSPC integrity and mitigate developmental and cognitive risks, especially in neonates exposed via breastfeeding.